Effects of the Enhancing Wisdom through Buddhist Doctrine Program on Hope and Coping in Terminally Ill Cancer Persons - Araya Jeranukul (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Hope and coping are major factors affecting quality of life in the terminally ill persons with cancer. Therefore, enhancing their hope and ability to cope with their illness can improve their quality of life. This two group pre-posttest experimental design aimed to investigate the effects of the Enhancing Wisdom through Buddhist Doctrine Program on hope and coping in terminally ill persons with cancer. A sample of 38 terminally ill Thai Buddhist persons with cancer, whose ages ranged from 40-70 years and who met the inclusion criteria were recruited for this study. The participants were randomly assigned into an experimental group or control group. The experimental group received the Enhancing Wisdom through Buddhist Doctrine Program consisting of a five-day training session and follow-up through home visits and telephone calls for four weeks, whereas the control group received standard care. The final sample for analysis included 33 participants, 15 in the experimental group and 18 in the control group. Data were collected at baseline, at the program end, one month after, and two months after the end of program using the Herth Hope Index and Jalowiec Coping Scale. These scales were chosen for their reliability and validity. Data were analyzed using descriptive statistics, one and two-way repeated measures ANOVA, and independent sample t- test. Results revealed that participants in the experimental group had significantly higher levels of hope over time at all follow-up time points - the program end, one month and two months after the end of program (p < .01) - as compared with hope measured at baseline. Following the program, levels of hope among the experimental group were significantly higher than for those receiving standard care at one month (p < .01) and two months post program (p < .01). With regards to coping, overall, the confrontive and palliative coping of participants in the experimental group did not significantly change over time, though emotive coping in this group was significantly lower at follow-up time points - at one month after and two months after (p < .01) - than before the program. After receiving the program, overall coping, confrontive and palliative coping of the experimental group was not significantly higher than those receiving standard care. However, emotive coping of the experimental group was significantly lower than that of the control group one month and two months following the program (p < .01). Study findings can be used as a guide for planning interventions to enhance hope and coping abilities of terminally ill persons with cancer. Additionally, further research is needed to implement the program in the home. It is also recommended that future studies employ a double-blind experimental design, use a larger sample size, and use a longer duration of follow-up to identify the long-term effects of the program.